Simple Model for Market Returns Distribution - Anh, Chu Thuy; Lien, Do Hong; Viet, Nguyen Ai (Communications in Physics, 2013)
It has been observed that at the large time scales the distributionof stock market returns is convergent from Boltzmann distribution to Gaussianasymptotic one. To explain this universal phenomenon, we propose a new andsimple dynamic model to describe this convergence by the time parameter inassociation with the introducing the concept of relaxation time for nancialmarkets. The analysis of stock market data packages in dierent time intervalsshowed that our model ts well the nancial market data. The meaning ofsocalled relaxation time has been qualitatively made clear, as a measure toestimate the stability of the market.